Behavior of Verval Violence in Online Game Players (Mobile Legend: Bang Bang) - Agus Agus; Kurniati Zainuddin; Muhrajan Piara (PT ARRUS Intelektual Indonesia, 2024)
Verbal violent behavior in the online game mobile legend: bang bang for some online game players is normal and has become a habit. The purpose of this study was to explore the behavior of verbal violence in online game players: mobile legend bang bang. This study uses a qualitative research design with a construct realism approach. The research respondents totaled 188 online game players: mobile legend: bang bang. Data was collected using an open question questionnaire. Data analysis was carried out in three stages, namely open coding, axial coding, and selective coding. The results of the study show that there are five types of verbal abuse that occur in online games: mobile legend: bang bang, i.e. swearing by demeaning one's abilities, using animal names, harsh words, sexual harassment, and swearing by insulting one's condition. The causes of individuals getting verbal violence are lack of skills, experiencing defeat in games, poor communication, and network disturbances. Individuals also verbally abuse other individuals due to anger, bad playing players, game atmosphere, habits, and game strategies. The individual goals of verbal violence are expressing frustration, motivating players, self-satisfaction, game strategies, and player habits. The impact of verbal violence is the psychological impact such as hurt, fear, giving resistance, provoked anger, and retaliating. Non-psychological impacts such as stopping playing, reporting to game parties, disabling communication features, and motivating players. Efforts to minimize verbal violence in the legendary mobile game: bang bang, namely reminding each other, playing seriously, calming down, stopping playing, venting on other things, ignoring other players. The implication of this research is as a source of literacy regarding verbal violence that occurs in the mobile game legend: bang bang.